PROFESSIONAL MURABBI IN MUHAMMADIYAH AND NAHDLATUL ULAMA (NU) EDUCATION - Maman A. Majid Binfas; Somariah Fitriani; Hasmawati Hasmawati (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2018)
The term of Murabbi is identified with the task of educating their students to be professionally creative and innovative. The root word of professionalism is a profession, which is in general understood as an inborn gifted talent from God to human being. Muhammadiyah and Nahdatul Ulama (NU) as the Islamic biggest organizations in the Republic of Indonesia, understand the issue of such talent, not solely on the principles of the religion, but it can be combined with modern science that advances education competencies. Competent education can develop common sense of the students, promote and enlighten their lives. This article has aimed at recognizing, elaborating and understanding professional Murabbi in term of Muhammadiyah and NU education. The study employed historical studies as a part of qualitative research in a descriptive model to obtain the actual reality. Depth interviews with some public figures from both Muhammadiyah and NU and document analysis were conducted to collect the empiric data. The research has revealed that education run by Muhammadiyah and NU has been inclined to the creation of the appropriate individual nature, and professional capability to become change of agents based on the advanced principles of Islamic teachings, which its aim is to enlighten humanity. Additionally, the essence of Muhammadiyah and NU education is to humanize humans, based on the essence of human nature itself that always spreads compassion and has principles to the roots of imanan wahtisaban Kemurabbian (believe wholeheartedly and hope to get reward from Allah, God Almighty) without exploiting their students.